The Influence of Competence and Job Satisfaction on Discipline which Implications for Employee Performance at Bank Jambi Muara Sabak Branch Office - Andhyka Pinang; Fakhrul Rozi Yamali; Ali Akbar (Journal of Accounting and Finance Management, 2026)
This study has several objectives, including analyzing and describing employee competency, job satisfaction, discipline, and performance at Bank Jambi Muara Sabak Branch Office. It also aims to determine and analyze the influence of competency and job satisfaction on employee performance, both directly and indirectly through work discipline. This research was conducted at the Muara Sabak Branch of Bank Jambi. The population consisted of 54 employees, using a census technique. This research employed a quantitative approach with a survey method and Partial Least Squares (PLS) data analysis. This study concludes that Bank Jambi Muara Sabak Branch Office has employees with high competence, high levels of job satisfaction, high work discipline, and high employee performance. Furthermore, competence and job satisfaction through work discipline have a positive and significant influence on employee performance at Bank Jambi Muara Sabak Branch Office. These findings indicate that employee job satisfaction plays a role in shaping better levels of work discipline, which in turn has a positive impact on employee performance.